2011
DOI: 10.1186/1471-244x-11-44
|View full text |Cite
|
Sign up to set email alerts
|

Short-term prediction of threatening and violent behaviour in an Acute Psychiatric Intensive Care Unit based on patient and environment characteristics

Abstract: Background: The aims of the present study were to investigate clinically relevant patient and environment-related predictive factors for threats and violent incidents the first three days in a PICU population based on evaluations done at admittance. Methods: In 2000 and 2001 all 118 consecutive patients were assessed at admittance to a Psychiatric Intensive Care Unit (PICU). Patient-related conditions as actuarial data from present admission, global clinical evaluations by physician at admittance and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 38 publications
1
17
1
2
Order By: Relevance
“…hjemmekoselig miljø enn nakent interiør, og at vanlig interiør reduserte tendensen til øde-leggelse av møbler (4,5,38). De fant videre at skjermingsavsnitt ga raskere symptomreduksjon ved ruslidelser (39).…”
Section: Virkninger Av Skjerming For Pasienter Og Personaleunclassified
See 1 more Smart Citation
“…hjemmekoselig miljø enn nakent interiør, og at vanlig interiør reduserte tendensen til øde-leggelse av møbler (4,5,38). De fant videre at skjermingsavsnitt ga raskere symptomreduksjon ved ruslidelser (39).…”
Section: Virkninger Av Skjerming For Pasienter Og Personaleunclassified
“…De fant videre at skjermingsavsnitt ga raskere symptomreduksjon ved ruslidelser (39). Noen studier viser at skjermingsavsnitt kan gi faerre trusler og mindre vold (5,6,40), andre at det å bli lukket inne på et rom kan skape konflikt, aggresjon og utagering (1,12,26).…”
Section: Virkninger Av Skjerming For Pasienter Og Personaleunclassified
“…Aggressive behavior is a matter of great concern in psychiatric services and should be a key priority in mental health settings [1][2][3]. Both the frequency of aggression and the strong negative impact on staff and patients are important considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Assaults on staff are unfortunately relatively common in psychiatric intensive care units (PICU) (Palmstierna et al 1991;Vaaler et al 2011). Aggressive behaviour is one of the most common reasons for transfer to a PICU (Bowers et al 2012) and one study found that one third of patients in a PICU committed an assault during their admission (Walker & Seifert, 1994).…”
Section: Introductionmentioning
confidence: 99%